ANALISIS IMPLEMENTASI STRATEGI PEMASARAN (Studi Kasus Pada Rumah Sakit Mata Pekanbaru Eye Center) - Marlia Janti Abdun; Okta Karneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to find out how to implement the marketing strategy at Pekanbaru Eye Center Eye Hospital. The sample in this study was taken as many as 4 respondents consisting of Key Informants, namely Marketing Managers and 3 supplementary information, namely patients Eye Center Pekanbaru Eye Hospital. The technique used is Snowball Sampling Technique. The data in this study using the Triangulation method through interviews with consumers. Data obtained from the results of interviews with Key Informants were then cross-checked with complementary informants and then processed to be tested with qualitative methods. The results of the analysis using qualitative data analysis, because the data obtained in the form of information. The results of this study indicate that the implementation of the marketing strategy of Pekanbaru Eye Center Eye Hospital has been successful.Keywords : Marketing Strategies, Marketing Implementation, Qualitative Research